Mechanical behavior and energy absorption capability of trigonometric function curved rod cell-based lattice structures under compressive loading - Linlin Zhang; Junwei Wu; Yuejing Zhao; Zhiying Qin (Scientific Reports)
Abstract Traditional body-centered cubic (BCC) lattice metamaterials exhibit structural deficiencies including geometric discontinuity at cell connections and pronounced stress concentration at nodal regions, which restrict further enhancement of mechanical performance. This study proposes a novel lattice design methodology utilizing trigonometric function-modulated strut axes, yielding three novel trigonometric function curved rod cell-based lattice structures (TCRC, SCRC, and CCRC). By integrating fillet transition technology to achieve stress redistribution optimization, these configurations were systematically upgraded to TCRC-ipv, SCRC-ipv, and CCRC-ipv variants with enhanced structural performance. Experimental specimens were fabricated using selective laser melting (SLM) additive manufacturing technique, and the static mechanical response mechanisms were systematically investigated through quasi-static compression tests coupled with nonlinear finite element method (FEM) simulations. Results demonstrate that the trigonometric function-based topology optimization strategy combined with nodal fillet design significantly enhances overall structural performance. The TCRC-ipv configuration exhibits optimal comprehensive mechanical properties: compared with the reference BCC structure, it achieves 39.2% enhancement in elastic modulus, 59.4% increase in peak compressive strength, and 46.1% improvement in yield strength. Additionally, the energy absorption stress plateau elevates by 10.3%, with specific energy absorption capacity remarkably augmented by 86.1%. The proposed multiscale collaborative optimization strategy establishes a new theoretical framework and technical pathway for topology optimization design of lattice metamaterials in engineering applications.